2020
DOI: 10.1007/s00277-020-04328-4
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in cancer patients: clinical characteristics and outcome—an analysis of the LEOSS registry

Abstract: Introduction Since the early SARS-CoV-2 pandemic, cancer patients have been assumed to be at higher risk for severe COVID-19. Here, we present an analysis of cancer patients from the LEOSS (Lean European Open Survey on SARS-CoV-2 Infected Patients) registry to determine whether cancer patients are at higher risk. Patients and methods We retrospectively analyzed a cohort of 435 cancer patients and 2636 non-cancer patients with confirmed SARS-CoV-2 infection, enrolled between March 16 and August 31, 2020. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
172
3
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(206 citation statements)
references
References 20 publications
14
172
3
8
Order By: Relevance
“…Although we did not find any prognostic association related to sex, it is known that severe cases of COVID-19 and mortality have been associated with male patients in different studies [16,18,19]. Two factors can explain our data: First, the high prevalence of female patients in the general scope of the population often referred to the PCU, as reported by studies carried out in the same place [5,13,20], and second, the high proportion of patients with breast tumors, a disease with a predominant female characteristic, being considered the most prevalent in this sample.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Although we did not find any prognostic association related to sex, it is known that severe cases of COVID-19 and mortality have been associated with male patients in different studies [16,18,19]. Two factors can explain our data: First, the high prevalence of female patients in the general scope of the population often referred to the PCU, as reported by studies carried out in the same place [5,13,20], and second, the high proportion of patients with breast tumors, a disease with a predominant female characteristic, being considered the most prevalent in this sample.…”
Section: Discussioncontrasting
confidence: 85%
“…Liu et al [ 15 ], through a meta-analysis, found that in six selected studies, the age > 65 years old was associated with an increased risk of death (relative risk (RR): 1.27; 95% CI: 1.08–1.49). According to Ruthrich et al [ 16 ], advanced age was associated with higher death rates in a cohort of 435 patients with cancer and confirmed SARS-CoV-2 infection, and enrolled between March 16 and August 31, 2020.…”
Section: Discussionmentioning
confidence: 99%
“…18 The primary endpoint was the efficacy of the vaccine in reducing the cases with laboratory-confirmed J o u r n a l P r e -p r o o f Cancer patients have been shown to be at a higher risk of severe COVID-19, possibly because of older age and more frequent comorbidities. 29 In particular, patients with haematological malignancies are at a persistently increased risk whereas solid tumor patients appear to suffer an increased risk mostly in the first year after diagnosis which drops to baseline >5 years after diagnosis. 30 For any malignancy, active disease confers a significantly increased risk of severe COVID-19.…”
Section: Vaccinationmentioning
confidence: 99%
“…Perspektivisch ist es sinnvoll, weitere mit Bezug auf COVID-19-Erkrankungen und damit verbundene pathologische Merkmale entwickelte klinische Register in die Datenintegration mit einzubeziehen. Das von der DGI (Deutsche Gesellschaft für Infektiologie) und dem DZIF (Deutsches Zentrum für Infektionsforschung) konzipierte „lean european open survey for SARS-CoV‑2 infected patients“ (LEOSS) sammelt europaweit Daten zu Epidemiologie und Krankheitsverlauf von Patienten mit COVID-19 ([ 49 ]; https://leoss.net ). Die Studie „pooled analysis of neurologic disorders manifesting in intensive care“ (PANDEMIC) der Deutschen Gesellschaft für Neurointensiv- und Notfallmedizin (DGNI) betrachtet die Charakteristika von COVID-19-Patienten mit neurologischen Manifestationen und gleichzeitigem schweren Verlauf ( https://www.dgni.de/forschung/ignite-initiative-klinischer-multizenter-studien.html ).…”
Section: Covid-19-registerunclassified